Daily dynamic of indicators of girl-students’ blood micro-circulation - Stanishevska, T.I.; Gorna, O.I.; Berezhniak, A.S.; Horban, D.D. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: study daily dynamic of indicators of girl-students’ blood micro-circulation. Material: 340 girls of 17-19 years old age were examined. The method of laser Doppler’s flow metering was used. Results: The state of tissue blood circulation was determined. Character of micro-circulation’s changes under influence of daily bio-rhythms was detected. In first half of day tension of mechanisms of micro-circulation’s regulation takes place. Partially it reduces by 4 p.m. at the account of strengthening of metabolic components of vasomotor rhythm. In evening period there is observed compensatory increasing of breathing and pulse modulations. It is connected with weakening of sympathetic and strengthening of parasympathetic impacts on tissue blood circulation. Also we registered changes in correlation of rhythmic components of tissue blood circulation’s oscillations at the accounts of weakening of vasomotor rhythm. It witnesses about tension of regulatory mechanisms. Conclusions: it is recommended to use the received data as normative indicators of laser Doppler’s flow metering when studying pathological processes.